Teleophthalmology Service During COVID-19 In Indonesia: Initial Reports - Valenchia Valenchia; Nina Asrini Noor; Martin Hertanto; Johan Hutauruk (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction: Due to difficulties in attending direct patient care and to limit the spread of COVID-19, the Indonesian ministry of health encourages hospitals to establish telemedicine services. This study aimed to report the initial practice of real-time teleophthalmology during the COVID-19 pandemic in Indonesia. Methods: This retrospective descriptive-analytical study collected data from patients who had teleophthalmology consultations within 3 months (April 27 – July 27, 2020). All consecutive patients were included in this study, except those with incomplete records. Patients’ demographics, the main reason for the consultation, working diagnosis, prescribed medication, management plan, and satisfaction survey were collected for the analysis. Result: There were 251 video consultations from 206 patients with 4 patients (1.9%) excluded due to incomplete medical records. There were 52 (25.7%) new patients. The median consultations were 2 (1-8) each day. The median age was 43.5 (from <1 year to 95 years). The main reasons for consultation were dry eye-related symptoms and red eye. The three most common primary working diagnoses were dry eye syndrome, conjunctivitis, and stye. Medication was prescribed for 149 patients (73.8 %) and 43 patients (21.3 %) were advised to have immediate direct consultation. The satisfaction survey revealed a 21.3% response rate, of which 41.9% and 58.1% felt very satisfied and satisfied respectively. Conclusion: Real-time teleophthalmology consultation seemed to be well-accepted by our population in spite of its early adoption with a high satisfactory rate.